Manajemen Perpustakaan Sekolah - Mansyur, Mohammad (Pustakaloka, 2015)
School library is one of the most important resource center to achieve the learning process, and increase the out come of learning. So it must be managed beter from now. This article tries to explore how to manage school library from human resources, collection, other devices. To implement management on library, it needs cooperation among other teacher, librarian, parent, school principal,Â  and student.